Renegotiation-Proof Relational Contracts with Side Payments - Sebastian Kranz; Susanne Ohlendorf (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We study infinitely repeated two player games with perfect information, where each period consists of two stages: one in which the parties simultaneously choose an action and one in which they can transfer money to each other. We first derive simple conditions that allow a constructive characterization of all Pareto-optimal subgame perfect payoffs for all discount factors. Afterwards, we examine different concepts of renegotiation-proofness and extend the characterization to renegotiation-proof payoffs.
urn:nbn:de:bvb:19-epub-13293-1
Keywords: C73; L14; 330; renegotiation; infinitely repeated games; side payments; optimal penal codes; Unvollständiger Vertrag; Verhandlungstheorie; Wiederholte Spiele; Schuldrecht; Theorie